Artificial Intelligence Accidentally Learned Ecology through Video Games. (July 2020) - Barbe, Lou; Mony, Cendrine; Abbott, Benjamin W.
Abstract : An advanced artificial intelligence (AI) system defeated the best human players in StarCraft II, a popular real-time strategy game. In a virtual ecosystem, players compete for habitats and resources, unintentionally reproducing many ecological phenomena. We propose to repurpose this AI to test ecological hypotheses that have been intractable using traditional approaches.